Metabolic biomarkers of risperidone-induced weight gain in drug-naïve patients with schizophrenia - Qiu, Yuying; Dong, Yeqing; Sun, Wei; Li, Gang; Li, Mei Juan; Zhao, Yongping; Jiang, Changyong; Li, Jie (Frontiers in Psychiatry, 2023)
Abstract Background: Risperidone is a commonly prescribed antipsychotic drug with a potential side effect of weight gain. However, the pathophysiological mechanism is still poorly understood. Here, we sought to identify potential biomarkers of risperidone-induced weight gain by using a targeted metabolomics approach. Methods: We enrolled 30 subjects who received risperidone monotherapy for 8 weeks from a prospective longitudinal cohort study for drug-naïve schizophrenia patients. Plasma metabolites were measured by targeted metabolomics Biocrates MxP® Quant 500 Kit at baseline and 8-week follow-up. Results: After 8 weeks of risperidone treatment, the levels of 48 differential metabolites were up-regulated, including lysophosphatidylcholines (2), phosphatidylcholines (PC) (8), cholesterylesters (CE) (3), and triglycerides (35), while 6 differential metabolites namely PC aa C38:6, methionine (Met), α-aminobutyric acid (AABA), TrpBetaine, CE (22:6) and Taurocholic acid (TCA) were down-regulated. Interestingly, the reduction of PC aa C38:6, AABA and CE (22:6) was linearly related with increased BMI. Further multiple regression analysis showed that the changes of PC aa C38:6 and AABA were independent contributors of increased BMI. In addition, baseline levels of PC aa C36:5, CE (20:5) and AABA had positive relationships with the change of BMI. Conclusion: Our findings indicate phosphatidylcholines and amino acids may serve as biomarkers for risperidone-induced weight gain